Pengaruh Budaya Organisasi Dalam Meningkatkan Produktivitas Kerja Dengan Motivasi Sebagai Variabel Mediasi Pada PT XYZ - Mutia Nurul Badriah; Siti Sarah (Cattleya Darmaya Fortuna, 2026)
With the intrinsic encouragement of PT XYZ employees as mediators, this study aims to explore the relationship between organizational norms and work productivity. The methodology used is quantitative and combines descriptive and verification approaches. The descriptive approach involves the description of the condition of the study variables, while the verification approach uses path analysis To test the relationship between factors, this study uses a full sampling approach. Saturated, 85 employees became the study population. According to research findings, organizational culture, work motivation, and productivity are all beneficial. There is no substantial direct correlation between organizational culture and work productivity levels, but there is a positive and significant relationship between work motivation and organizational culture. Increased productivity is best achieved by increasing employee enthusiasm, which in turn is driven by a positive company culture, as research shows that employee motivation can moderate the influence of company culture on productivity.